تغيرات صيغة خلايا الدم البيض وأشكالها أثناء الإصابة وبعد الشفاء من داء الليشمانيا الجلدية عند الإنسان( دراسة مقارنة) - ديب ندى; مرة محمد; سلمان حسن (Latakia University Journal -Biological Sciences Series, 2017)
أجريت الدراسة الحالية على عينات دم تعود لـ 15مريضاً (12 ذكور, 3 إناث ) ممن شخصت إصابتهم بالليشمانيا الجلدية و ثبت شفاؤهم منها بعد الخضوع للعلاج الموضعي. وأجريت اختبارات الدراسة على مرحلتين: الأولى بعد الخمج، والثانية بعد شهرين على الأقل من الشفاء. وخضع كل مريض في كلا المرحلتين للاختبارات الآتية: التعداد الكلي والعد التمييزي لخلايا الدم البيض, وقياس قيمة الهيماتوكريت. إضافة لذلك، تم إجراء دراسة للتغيرات المورفولوجية لخلايا الدم البيض للمصابين. أظهرت نتائج المرحلة الأولى ارتفاعاً معنوياً في متوسط تعداد اللمفاويات والحمضات (P<0.05) ترافق مع انخفاض معنوي( ذو دلالة إحصائية) في متوسط التعداد الكلي لخلايا الدم البيض ونسبة العدلات (P<0.01) ومتوسط قيمة الهيماتوكريت (P<0.01)مقارنةً مع القيم الطبيعية. أما في المرحلة الثانية فقد بينت النتائج عودة نسبة خلايا الدم البيض إلى قيمها الطبيعية حيث لوحظ انخفاض معنوي في تعداد الحمضات (P<0.05) وانخفاض غير معنوي في تعداد اللمفاويات( P>0.05)، وكذلك ارتفاع غير معنوي في التعداد الكلي لخلايا الدم البيض ( P>0.05). كما أظهرت المقارنة بين نتائج المرحلتين الأولى والثانية فروقاً معنوية في التعداد الكلي وتعداد الحمضات، بينما لم تكن هذه الفروق معنوية بالنسبة للعدلات، واللمفاويات، والوحيدات ( P>0.05). أما بالنسبة للدراسة المورفولوجية الخلوية فلم تظهر النتائج أي اختلاف جوهري بين خلايا الدم البيض لدى الأشخاص المصابين وغير المصابين بالليشمانيا الجلدية. The present study was performed on blood samples belong to 15 patients( 12 males,3 females) infected with cutaneous leishmaniasis, and their healing was also proved after submitting local treatment. Study tests were performed on 2 stages, the first after infection, and the second two months at least after healing. Every patient was subject of the following tests: total, and differential white blood cells count and hematocrit value. In addition ,a study of the morphological changes of white blood cells was conducted. The results of the first stage have showed a significant increasing in lymphocytes and eosinophils mean percent) P<0.05) accompanied with significant decreasing in total white blood cell count, neutrophils mean percent(P<0.01), and mean hematocrit value (P<0.01) in comparing with the normal values. In the second stage of study, the results have demonstrated a reconversion of white blood cells mean percent into their normal levels,whereas a significant decreasing in eosinophils mean percent (P<0.05), and no significant decreasing in lymphocytes mean percent (P>0.05), and also no significant increasing in total blood cell count(P>0.05). Comparison between the results of the two stages have showed a significant difference in total white blood cell count, and eosinophils count, while these differences were not significant for neutrophils ,lymphocytes , and monocytes(P>0.05).. Concerning the cell morphological study, the data have not showed any noticeable differences between white blood cells of infected and uninfected human with cutaneous leishmaniasis .